CompTIA A+ certification all-in-one exam guide (exams 220-1101 & 220-1102) - Everett, Travis A.; Hutz, Andrew (McGraw Hill-Ascent Audio, 2023)
This fully revised and updated resource offers complete coverage of the latest release of CompTIA A+ exams 220-1101 and 220-1102. You'll find learning objectives at the beginning of each chapter, exam tips, practice exam questions, and in-depth explanations. Designed to help you pass the CompTIA A+ exams with ease, this definitive guide also serves as an essential on-the-job IT reference. Covers all exam topics, including how to: work with CPUs, RAM, BIOS, motherboards, power supplies, and other personal computer components; install, configure, and maintain hard drives; manage input devices and removable media; set up, upgrade, and maintain Microsoft Windows; troubleshoot and fix computer problems; install printers and other peripherals; configure and secure mobile devices; connect to the Internet; set up wired and wireless networks; protect your personal computer and your network; and implement virtualization and cloud-based technologies. Online content includes: practice exams for 1101 and 1102 with hundreds of questions; one hour of video training from Mike Meyers; TotalSim simulations of performance-based questions; and a collection of Mike Meyers's favorite shareware and freeware PC tools and utilities.
Online resource; title from title details screen (O'Reilly, viewed June 20, 2023)
Keywords: Computing Technology Industry Association -- Study guides -- Examinations; Computer technicians -- Study guides -- Certification; Electronic data processing personnel -- Study guides -- Certification; Microcomputers -- Study guides -- Maintenance and repair -- Examinations; Computing Technology Industry Association; Micro-ordinateurs; Entretien et réparations; Examens; Guides de l'étudiant; Computer technicians; Certification; Electronic data processing personnel; Certification; Examinations; Microcomputers; Maintenance and repair; Examinations; examination study guides; Audiobooks; Study guides; Livres audio; Guides de l'étudiant